REACHING ASYNCHRONOUS LEARNERS WITHIN THE SILVER TSUNAMI - Ettinger, Linda F. (Online Learning, 2006)
This paper provides a profile of the population niche known as baby boomers, seniors and retired, collectively called the silver tsunami, relative to the potential for growth of the number of asynchronous online learners. General contextual information concerning population statistics, computer use and access trends, prefaces a listing of learning in retirement programs associated with institutions of higher education in the United States.